2019
DOI: 10.1590/0100-29452019072
|View full text |Cite
|
Sign up to set email alerts
|

Fruit set and yield of apple trees cv. Gala treated with seaweed extract of ascophyllum nodosum and thidiazuron

Abstract: The low effective fruiting is one of the biggest problems of apples’ production in Brazil and its main cause involves the process of pollination. The objective was to evaluate the fruit set and production of apple trees cv. Gala treated with extract of seaweed Ascophyllum nodosum and thidiazuron. The experiment was carried out during two cycles (2015/2016 and 2016/2017) in Porto Amazonas, State of Paraná, Brazil, with apple trees cv. Gala. The following treatments were applied at full bloom: thidiazuron at 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…The total soluble solids content (Table 3) showed similar values between the control, LG, and MA, while PEP reported a lower value of about 5.35% compared to the other treatments. Similar results have also been observed by Bradshaw et al [31] and by De Sousa et al [32], in which ANE (Ascophyllum nodosum extracts) treatment had no effect on fruit firmness, starch index at harvest, and soluble solids concentration. Whereas, in agreement with Robert and von Loeska [33], TSS showed an increase of 9.9% from the harvest to +120 days of cold storage, while in contrast to TSS, a reduction in titratable acidity of 49.3% was registered.…”
Section: Effects Of Biostimulants On Flesh Firmness Total Soluble Solids Content Total Acidity and Juice Phsupporting
confidence: 88%
“…The total soluble solids content (Table 3) showed similar values between the control, LG, and MA, while PEP reported a lower value of about 5.35% compared to the other treatments. Similar results have also been observed by Bradshaw et al [31] and by De Sousa et al [32], in which ANE (Ascophyllum nodosum extracts) treatment had no effect on fruit firmness, starch index at harvest, and soluble solids concentration. Whereas, in agreement with Robert and von Loeska [33], TSS showed an increase of 9.9% from the harvest to +120 days of cold storage, while in contrast to TSS, a reduction in titratable acidity of 49.3% was registered.…”
Section: Effects Of Biostimulants On Flesh Firmness Total Soluble Solids Content Total Acidity and Juice Phsupporting
confidence: 88%
“…An increase in the quality of grape berries in the study of [36] was obtained after the application of a mixture of seaweed extract together with lime and magnesium. A positive effect on the apple weight after the application of such biostimulants was also demonstrated by [37] while [38] showed no effect of Goëmar BM 86 formulation based on marine algae extract on the average weight of single fruit and total yield in apple crops.…”
Section: Resultsmentioning
confidence: 85%
“… Yang et al (2023) found the foliar application of SE improved the levels of soluble solids, Vitamin C, free amino acids, sugars, and mineral elements in the fruits. Likewise, Ayub et al (2019) reported that SW applied to ‘Gala’ apple at concentrations ranging from 0.1% to 0.6% resulted in higher fruit set percentage, total fruit numbers, fruit weight, and fruit length compared to the control, with the 0.3% concentration yielding the best results. Alebidi et al (2021) reported that spraying algae on Barhee date palm enhanced the physical and chemical properties of the fruit and yielded the highest values of fruit length, fruit diameter, fruit shape index, flesh weight, seed weight, total soluble solids (TSS), acidity, TSS/acid ratio, tannins, reducing sugars, nonreducing sugars, and total sugars.…”
Section: Discussionmentioning
confidence: 93%